2020
DOI: 10.54393/tt.v1i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Uterus Prolapse in Pregnant Females of Lahore: A Cross-sectional Survey

Abstract: Uterus prolapse is a common gynecological condition which is relatively less common during pregnancy. Prolapse maybe conceptualized as a type of herniation or bulge of the pelvic organs into or out of the vagina because of damage or weakness of connective tissues and muscles of pelvic floor area Objective: The objective was to determine the prevalence of uterus prolapse among pregnant females. Methods: This cross-sectional study was conducted in pregnant females. Sample size of 189 was calculated. Standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…It was responded the majority (36.56%) of respondents that UP is caused due to weakness in pelvic muscles followed by delivery by an unskilled person (27.58%), giving birth at an early age (20.68%), frequent childbearing (10.68%), and constipation (4.48%) as given in Table 2. Many similar factors have been reported by many early researchers 16 . They reported that UP is the main issue in communities where parity is high, pre-existing family history, childbearing starts earlier, proceeding age, high body mass index, obesity, and constipation.…”
Section: Resultssupporting
confidence: 81%
“…It was responded the majority (36.56%) of respondents that UP is caused due to weakness in pelvic muscles followed by delivery by an unskilled person (27.58%), giving birth at an early age (20.68%), frequent childbearing (10.68%), and constipation (4.48%) as given in Table 2. Many similar factors have been reported by many early researchers 16 . They reported that UP is the main issue in communities where parity is high, pre-existing family history, childbearing starts earlier, proceeding age, high body mass index, obesity, and constipation.…”
Section: Resultssupporting
confidence: 81%